2005
DOI: 10.1063/1.2105998
|View full text |Cite
|
Sign up to set email alerts
|

High-strength Ti-base ultrafine eutectic with enhanced ductility

Abstract: ( Ti 0.705 Fe 0.295 ) 100 − x Sn x (x=0 and 3.85) ultrafine eutectics were prepared by slow cooling from the melt through cold crucible casting. The addition of 3.85 at. % Sn to the binary Ti–Fe eutectic decreases the strength slightly but considerably improves the plastic deformability under uniaxial compressive loading from εf=2.1% to 9.6% strain to failure. The change in the morphology of the eutectic and the distribution of the FeTi phase are suggested as origin of the improvement of the mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
106
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 14 publications
4
106
0
Order By: Relevance
“…It has been already reported that Ti 70.5 Fe 29.5 exhibits no plasticity under compression and usually breaks into multiple pieces under unconstrained geometry with a specimens aspect ratio of height: diameter of 2:1. 8 However, some plasticity can be obtained under constrained geometry. 13 Furthermore, it has been reported that addition of Sn refines the interlamellar spacing of Ti 70.5 Fe 29.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been already reported that Ti 70.5 Fe 29.5 exhibits no plasticity under compression and usually breaks into multiple pieces under unconstrained geometry with a specimens aspect ratio of height: diameter of 2:1. 8 However, some plasticity can be obtained under constrained geometry. 13 Furthermore, it has been reported that addition of Sn refines the interlamellar spacing of Ti 70.5 Fe 29.…”
mentioning
confidence: 99%
“…Recently, homogeneous ultrafine composites without any micrometer-size second phase dispersions has been developed in Ti-Fe-Sn, 8,9 Fe-Nb-Al, 10 and Ni-Zr alloys. 11 The deformation mechanism on the improvement of plasticity has been explained due to the change in morphology of the phases upon ternary alloy additions, 9 which helps formation of large number of shear bands, 8,9,12 their rotation 10,11,13 or phase transition. 14 In this letter, we report on the microstructure evolution in differently deformed Ti 68.38 Fe 28.61 Sn 3 ultrafine composites to explore the mechanism of plastic deformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FeTi is a thermodynamically stable [10][11][12] nonmagnetic [13] intermetallic compound with a bcc-based B2 structure and a melting point of approximately 1600 K. FeTi is of interest for its hydrogen absorption capabilities [14][15][16] and for its mechanical properties [17,18]. It has been the subject of a large number of experimental and theoretical studies including inelastic neutron scattering [19,20] and first-principles calculations [21][22][23].…”
mentioning
confidence: 99%
“…Recently a novel temperature-induced ETT has been reported to alter magnetoresistivity [9]. In this Letter, we show through first-principles calculations and ancillary experiments how a thermally driven ETT drives anomalous changes in phonon dynamics.FeTi is a thermodynamically stable [10-12] nonmagnetic [13] intermetallic compound with a bcc-based B2 structure and a melting point of approximately 1600 K. FeTi is of interest for its hydrogen absorption capabilities [14][15][16] and for its mechanical properties [17,18]. It has been the subject of a large number of experimental and theoretical studies including inelastic neutron scattering [19,20] Forces and atomic configurations in the AIMD simulations were used to compute phonon energies at different temperatures with the temperature-dependent effective potential (TDEP) method [47,48], in which a model HamiltonianĤ…”
mentioning
confidence: 99%